MAXIMUM DISCLOSURE WITH MINIMUM DELAY - Van R. du Preez, J (Scientia Militaria - South African Journal of Military Studies, 2012)
In his treatment of the subject 'Die SA Weermag moet ook sy ander wapens effektief aanwend' in 7/1 issue of Militaria Colonel W. Otto regards it as incumbent on the South African Defence Force to make effective use of propaganda (in my book the corruption of the channels of communication).